Heterotopic adrenal tissue in a specimen after unilateral salpingo-oophorectomy: a case report - Dominika Trojnarska; Ewa Zabiegło; Robert Jach (Journal of Medical Case Reports)
Abstract Background Heterotopic adrenal tissue is an extremely rare finding. The most common site is the genitourinary tract and pelvis, more frequently in male than female children. In our report, we discuss an ectopic adrenal tissue detected incidentally in a perimenopausal woman, which is even more unusual. Case presentation A 54-year-old Eastern European perimenopausal female patient was referred for surgical treatment due to a suspected 60 mm paratubal cyst. Her medical history was unremarkable and risk of ovarian malignancy algorithm score were normal. Laparoscopic left salpingo-oophorectomy was performed and the specimen was sent for histopathology. The examination revealed a normal ovary, a fallopian tube with a simple paratubal cyst, and a 2.5 mm nest of heterotopic adrenal tissue in the nearby fat tissue. The patient was discharged on the first postoperative day, reported no symptoms, and remained asymptomatic at 3-week follow-up. Conclusion A review of the available English literature confirmed the rarity of heterotopic adrenal tissue in adult women. This case is presented due to its uniqueness, with the aim of raising awareness about the entity we encountered and presenting its possible implications.